Implicit and Explicit False Memories conditioned by lapse of time - Andreea HOROIȚĂ; Adrian OPRE (Studia Universitatis Babeş-Bolyai. Psychologia-Paedagogia)
False memories represent distorted memories which are remembered incorrectly or didn’t happen at all in reality. In the present study, the period of time between encoding and testing has been manipulated, in order to explore the effects of delay on implicit and explicit false memories. Two groups of subjects were tested, using the DRM paradigm, for false implicit and explicit memories. One group had no delay period between encoding and test phases, the other group was tested at one week delay after the encoding phase. Results showed no significant differences between implicit and explicit false memories. The delay had significant effect only for true memories, which were significantly lower after one-week delay. Conclusions and future directions of research are discussed.